Study on Titanium Oxide in Ceramics - Voica, Cezara (Current Approaches in Science and Technology Research Vol. 10, 2021)
This study presents the experimental works for obtaining ceramic glazes with a quality higher than those applied until now and a complex study of their properties for producing bone china articles. Starting from the composition of a glossy transparent glaze for bone china, an experimental study on obtaining opaque glazes has been worked out, by using in excess some components able to devitrify the basic glaze. The influences of titanium and calcium oxide and their mixture on the aspect, phase composition and thermal behavior in bone china glaze, have been investigated, with aim at obtaining the opaque crystallized glazes with high aesthetic effect. It has been shown that all the sintered glazes, exhibited a significant crystalline structure, which was confirmed by optical microscopy as well. There are recommended as extremely favorable cumulated of these oxides, summing up to 20%. The products obtained presented proper characteristics under normal thermal treatment conditions. There are surely expensive, but they only can be used for certain products that need a more sophisticated aspect justifying their use.